PENGARUH GIBERELIN TERHADAP PERKECAMBAHAN BENIH DAN PERTUMBUHAN SEMAI KAWISTA (Feronia Limonia (L.) Swingle) - Endang Dewi Murrinie; Untung Sudjianto; Khoirinnidha Ma’rufa Ma’rufa (Universitas Muhammadiyah Purwokerto, 2021)
Wood-apple is a rare plant that is almost extinct, so efforts are needed to increase the population. Wood-apple is generally propagated generatively. Wood-apple seeds need 2-3 weeks to germinate, so when germinated many seeds are rotten before germination. Soaking in gibberellins is one way that can be done to shorten germination. The study aimed to determine the effect of concentration and duration of soaking in gibberellins on germination and growth of wood-apple seedlings. The study consisted of two factors which were designed in a completely randomized design. The first factor was the concentration of gibberellins, consisting of three levels, namely 25 ppm (k1), 50 ppm (k2), and 75 ppm (k3). The second factor was soaking time, consisting of three levels, namely 6 hours (l1), 9 hours (12), and 12 hours (13), so there were 9 treatment combinations and one treatment without gibberellins (control), each treatment was repeated three times. The results showed that the gibberellin treatment increased the height of the seedlings compared to the control. The concentration of gibberellins affects the length and diameter of the hypocotyl and the length of the radicle. Concentrations of 50 and 75 ppm resulted in higher hypocotyl diameter and radicle length than 25 ppm. The concentration of 75 ppm gave the highest hypocotyl length. Soaking time affects the percentage of germination, germination rate, and growth rate of wood-apple seedings. Soaking in gibberellins for 12 hours gave a faster growth rate of seedlings than 6 and 9 hours.